PENGARUH MODIFIKASI PERMAINAN TERHADAP TEKNIK DASAR BOUNCE PASS BOLA BASKET SMPN 8 PONTIANAK - Suja, Ferdianto; Simanjuntak, Victor; Hidasari, Fitriana Puspa (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstract This research intend to knowÂ  the influence of the game modification to basic technique bounce pass basket ball on student class VIII Senior High School 8 Pontianak. The Method of research used is experiment research with form of research true experimental design. Population in this research is class VIII as much 6 class. Taking sampling in this research used purposive sampling technique, that is grade VIII C amount 35 people as control class and class VIII D as experiment class. Data analysis do with computerization system and analysis by using t-test. Based on results t-test on control class and experiment results available p value = 0.000 <0.05, then Ho rejected (Ha Accepted), that mean there is an increase, where from value difference mean on experiment class (28,65) bigger than on control class (8,75).Keywords: Modification, Bounce Pass, Basket BallÂ